Sosialisasi Permainan Picleball di SDN 1 Tilango Kabupaten Gorontalo - Said, Hariadi (Universitas Negeri Gorontalo, 2024)
Sports activities are an important component in supporting children's physical, mental, and social development. Pickleball, a sport that combines elements of tennis, badminton, and ping pong, offers an interesting alternative to physical education in elementary schools. The socialization of pickleball at SDN 1 Tilango, Gorontalo Regency aims to introduce this sport to students and teachers through theory, practice, and game simulations. The activity method involves three stages: introduction to theory (cognitive domain), playing experience (affective domain), and real practice (psychomotor domain). The results showed an increase in students' understanding of the rules and basic techniques of pickleball, an increase in interest in sports, and the development of positive characters such as discipline, cooperation, and sportsmanship. This activity enriches students' insights into the variety of sports and provides a fun and useful experience. In addition, this program supports the national education goal of creating a healthy and characterful generation and contributes to the development of an inclusive sports culture in Indonesia.